Developmental and functional relationships between hypothalamic tanycytes and embryonic radial glia - Fong, Harmony; Kurrasch, Deborah M. (Frontiers in Neuroscience, 2023)
The hypothalamus is a key regulator of several homeostatic processes, such as circadian rhythms, energy balance, thirst, and thermoregulation. Recently, the hypothalamic third ventricle has emerged as a site of postnatal neurogenesis and gliogenesis. This hypothalamic neural stem potential resides in a heterogeneous population of cells known as tanycytes, which, not unlike radial glia, line the floor and ventrolateral walls of the third ventricle and extend a long process into the hypothalamic parenchyma. Here, we will review historical and recent data regarding tanycyte biology across the lifespan, focusing on the developmental emergence of these diverse cells from embryonic radial glia and their eventual role contributing to a fascinating, but relatively poorly characterized, adult neural stem cell niche.